PERBEDAAN INTERVAL WAKTU PEMBERIAN CAMPURAN Lactobacillus plantarum DAN KUNYIT DALAM AIR MINUM TERHADAP BOBOT KARKAS DAN LEMAK ABDOMEN BROILER - Wahid, Hijrul; Manin, Fahmida; Yusrizal, Yusrizal; Insulistyowati, Anie; Rahayu, Pudji; Viastika, Yanita Mutiaraning (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2025)
Abstract This study aimed to evaluate the effect of different intervals of administering a mixture of Lactobacillus plantarum and turmeric in drinking water on carcass weight and abdominal fat of broiler chickens. The research was conducted for 35 days at the Animal Production and Forage Laboratory, Faculty of Animal Science, University of Jambi, using 200 Lohmann Platinum (MB 202) day-old chicks of mixed sex. A Completely Randomized Design (CRD) was applied, consisting of four treatments and five replications, with 10 birds per replicate. The treatments were: P0 = drinking water without additives; P1 = 2% mixture of L. plantarum and turmeric administered daily; P2 = every two days; P3 = every three days. The mixture ratio of L. plantarum to turmeric was 3:1, given at 2% per liter of water. Observed parameters included feed and water intake, slaughter weight, carcass weight (absolute and relative), and abdominal fat (absolute and relative). Data were analyzed using ANOVA. Results showed no significant differences (P>0.05) among treatments for all parameters. However, the two-day interval treatment (P2) tended to improve slaughter and carcass weights while reducing abdominal fat compared to other treatments.